Effect of welded joint imperfection on the load-carrying capacity of pipe elbows subjected to in – plane bending moment - Medjo, Bojan; Rakin, Marko; Arsić, Miodrag; Damnjanović, Ivana; Stefanović, Ana; Grabulov, Vencislav (Journal of Engineering & Processing Management, 2021)
The defects in pipe elbows can, depending on their size and position, affect the integrity and safe service, as well as deformation ability of the piping systems in exploitation. Incompletely filled groove, which is the type of defect examined here, was observed by ultrasonic measurement on the pipeline in the regulation system of the hydro power plant Djerdap. Three-dimensional finite element analysis is performed using Simulia Abaqus software package. First, the models with dimensions of the defects observed by non-destructive examination are formed. Stress and strain fields for different loading types are shown and commented. The influence of the defect dimensions on the pipe elbow load-carrying capacity is determined through plastic collapse loads, which are obtained from bending moment - rotation angle diagrams. Twice elastic slope (TES) technique is applied. Additionally, some more severe defects are considered, in the form of sharp pre-cracks at the bottom of the defect; plastic collapse loads are also determined for these geometries. Both opening and closing bending moments are taken into consideration and the results are discussed and compared to two closed-form solutions from the literature. The influence of the boundary conditions applied for examination of the pipe elbows is commented.